Growth and production of chili (Capsicum annuum L.) on the application of Trichoderma sp. and Azolla liquid organic fertilizer. Issue 1 (April 2020) - Dungga, N E; Syaiful, S A; Alfiani, A; Amin, A R; Dachlan, A; Sahur, A; Dermawan, R; Idris, A I
Abstract: This study aimed to determine the response of the application Trichoderma sp. and Azolla as liquid organic fertilizer on the growth and production of chili ( Capsicum annuum L.) plants. The study was conducted in Panyili Village, Palakka District, Bone Regency, South Sulawesi Province, from October to December 2017. The research was conducted in the form of an experiment using a split plot design. Two levels of Trichoderma sp. application were set as main plots consisted of control and application of 4 g per plant Trichoderma asperellum . Application of Azolla as liquid fertilizer was set as sub plot with five doses, namely control, 15, 30, 45, 60, and 75 ml L −1 . The results show that application of Trichoderma asperellum 4 g per plant showed the best results on the number of leaves 70 days after planting (DAP) (272.22 leaves). Azolla liquid organic fertilizer (75 ml L −1 ) resulted in the highest production per plot at harvest period of I-III (1.28 kg/m 2 ), production per hectare at harvest period of I-III (4.27 tons ha −1 ). The interaction between Trichoderma asperellum 4 g plant −1 with a dose of Azolla liquid organic fertilizer of 75 ml L −1 showed the lowest attack intensity of aphids (10%).